Investigação das correlações dos polimorfismos dos genes da IL-6, TNF, IL-1Β, IL-10, e IL-17A com a gravidade e desfecho clínico da Covid-19 - Domingues, Otávio Brito (2024)
The SARS-CoV-2, which caused the COVID-19 pandemic, is a virus that primarily affects the respiratory system, with evidence of tropism for other organs. The manifestations of the disease are divided in terms of severity: in the mild form, the main symptoms include runny nose, sore throat, and cough accompanied or not by fever, muscle pain, loss of smell, loss of taste, headache, fatigue; in the moderate form, there may be pneumonia without complications, persistent daily fever, persistent cough, worsening of prostration and loss of appetite; the severe form is evidenced by Acute Respiratory Distress Syndrome; and the critical form is characterized by severe respiratory failure, severe pneumonia, dysfunction in various organs, acute respiratory distress syndrome, ICU admission, and need for respiratory support. In Brazil, COVID-19 resulted in more than 37 million cases and more than 700,000 deaths. The pathogenesis of the disease that SARS-CoV-2 causes not only involves direct cellular injury by the replication, but also an excessive production of pro-inflammatory cytokines, leading to widespread inflammation and tissue damage. The literature highlights the role of genetic variations in the host and their consequence in the evolution of viral diseases; the study of genetic variability of cytokines associated with the cytokine storm allows us to understand and identify the risk alleles and genotypes for this condition in the included population. This study investigated the role of single nucleotide polymorphisms in the severity and clinical outcome of COVID-19 in patients from the State of Ceará, recruited in the year 2021. The study population was divided into two groups, both unvaccinated: severe (n=82) and Mild/Moderate (n=40). The Severe group was subdivided into patients who evolved to death (n=33) and those who were discharged from the hospital (n=49). Whole blood samples were collected and DNA was extracted, quantified and then standardized. The genotyping of the SNPs was performed using the real-time polymerase chain reaction technique with TaqMan™ hydrolysis probes. The following SNPs were analyzed: IL 6 (rs1800795), TNF (rs1800629), IL-1β (rs1143627), IL-10 (rs1800872), and IL-17A (rs3819025). The relative frequency was analyzed through Fisher’s exact tests or Pearson’s chi-square test criterion p less (<) than 0.05. Binary logistic regression was used to predict disease severity based on comorbidities and alleles. In addition, it was also applied to predict severity considering the interaction between comorbidities and polymorphic alleles, using criterion p <0.05. Finally, binary logistic regression was employed to predict the occurrence of deaths based on comorbidities and alleles. A frequency difference was observed in relation to sex in the Severe and Mild/Moderate groups (p= 0.0009). However, no difference was found in relation to sex and outcome (p= 0.4899). Indicating that males have a higher susceptibility to the severe form of the disease. A difference was evidenced in relation to age in the Severe and Mild/Moderate group (p= <0.0001), as well as between age and outcome (p= 0.0411). This suggests that, with advancing age, the chances of developing the severe form of the disease and of evolving to death increase. No polymorphism was associated with severity and clinical outcome in the codominant, dominant and allelic models (p= >0.05). Individuals with the mild/moderate form of the disease presented a high frequency of individuals without Systemic Arterial Hypertension compared to the other groups (p= 0.013), but there was no significance for Diabetes Mellitus (p= 0.117). Binary logistic regression evidenced that the Systemic Arterial Hypertension model was significant, indicating that patients with this comorbidity have more than four times more chances of developing the severe form of COVID-19 (p = 0.003; OddsRatio= 4.42; CI 95%= 1.7 – 11.7). It also evidenced an interaction between Systemic Arterial Hypertension and Diabetes Mellitus. Patients with both comorbidities have more than ten times more chances of evolving to the severe form of COVID-19 (p= 0.025; OddsRatio= 10.52; CI 95% 1.35 – 81.99). An interaction was observed between Systemic Arterial Hypertension and the C allele of rs1800795, which increases by just over seven times the chance of developing the severe form of COVID-19 (p= 0.011; OddsRatio= 7.09; CI 95%= 1.58 – 31.84). There was also interaction with the G allele of rs1800872, increasing by more than three times the chance of evolution to the severe form of the disease (p= 0.015; OddsRatio= 3.65; CI 95%= 1.29 – 10.35). In addition, there was an interaction with the A allele of rs1143627, increasing by more than eight times the chances of developing the severe form of COVID-19 (p= 0.004; OddsRatio= 8.92; CI 95%= 2.0 – 39.78). Binary logistic regression did not reveal significance to predict death based on comorbidities and alleles (p= >0.05). In conclusion, the male sex is a factor that increases the predisposition to the severe form of COVID-19. In addition, age is a factor that increases the predisposition to both the severity of the disease and the evolution to death. The diagnosis of Systemic Arterial Hypertension increases the risks of developing the severe form of COVID-19. If the patient also has Diabetes Mellitus, the risk significantly increases. In addition, the presence of Systemic Arterial Hypertension and the C alleles of IL6, G of IL-10 and A of IL-1β also increase the predisposition to the severity of COVID-19. Therefore, it is crucial to closely monitor patients with these conditions and alleles.